2021
DOI: 10.1016/j.jns.2020.117224
|View full text |Cite
|
Sign up to set email alerts
|

Statin treatment and cerebral microbleeds: A systematic review and meta-analysis

Abstract: Although statins have been associated with increased risk of spontaneous intracerebral hemorrhage, their relationship with cerebral microbleeds (CMBs) formation is poorly understood. We systematically reviewed previously published studies reporting on the association between CMBs presence and current statin use.We performed a systematic search in MEDLINE and SCOPUS databases on October 24, 2019 to identify all cohorts from randomized-controlled clinical trials or observational studies reporting on CMB prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Statins could additionally mitigate the contribution of concurrent atherothrombotic vascular disease to the accrual of covert infarcts. A recent meta-analysis of mostly observational datasets reported an association between statin use and lobar cerebral microbleeds, 44 whereas another confined to randomized trials reported a reduction in the accrual of new covert infarcts with statin therapy. 45 The progression of white matter hyperintensities over time has been associated with increased risk of dementia and cognitive decline.…”
Section: Hmg-co a Reductase Inhibitors (Statins)mentioning
confidence: 99%
“…Statins could additionally mitigate the contribution of concurrent atherothrombotic vascular disease to the accrual of covert infarcts. A recent meta-analysis of mostly observational datasets reported an association between statin use and lobar cerebral microbleeds, 44 whereas another confined to randomized trials reported a reduction in the accrual of new covert infarcts with statin therapy. 45 The progression of white matter hyperintensities over time has been associated with increased risk of dementia and cognitive decline.…”
Section: Hmg-co a Reductase Inhibitors (Statins)mentioning
confidence: 99%
“…A large meta-analysis of 42 trials revealed no apparent association between statins and risk of ICH and showed a reduction in stroke and cerebral infarction [88]. Although several studies have been conducted on statin use and cerebral microbleeds (CMBs) formation, which are related to ICH, there is no clear association [89,90]. In addition, a large prospective cohort study suggested that statins might reduce the risk of ICH [91].…”
Section: Intracerebral Hemorrhagementioning
confidence: 99%
“…A recent meta-analysis examined the relationship between statin use and the development of CMBs. 23 It included seven studies (n=3,734 participants, with an unselected general population [n=1,965], patients with ischemic stroke [n=849], patients with hemorrhagic stroke [n=252], and patients with hypertension aged >60 years [n=668]). The results showed that statin use was not associated with CMBs in either unadjusted (OR, 1.15; 95% CI, 0.76 to 1.74) or adjusted analyses (OR, 1.09; 95% CI, 0.64 to 1.86).…”
Section: Lipid-lowering Therapy In Patients With Intracerebral Hemorrhagementioning
confidence: 99%